Collective wage regulation in northern Europe under strain: Multiple drivers of change and differing responses. (December 2018) - Dølvik, Jon Erik; Marginson, Paul; Alsos, Kristin; Arnholtz, Jens; Meardi, Guglielmo; Müller, Torsten; Trygstad, Sissel
There has been much recent attention to the upheavals, often externally induced, in collective bargaining and labour market regulation in southern European countries. In this article, we introduce a set of studies of changes, typically employer-driven, in collective wage regulation in northern Europe. We discuss possible drivers of change: contagion from southern Europe, regime competition among the northern countries themselves and/or destabilizing effects of east–north integration, driven by free movement. These drivers interact with internal change dynamics spurring diverging actor responses and institutional outcomes. We outline the common research design, review salient features of wage regulation in six countries, and differences in institutions, production, markets and factor mobility in four sectors. We briefly review findings from the other articles.